Implementing Collaborative Planning Forecasting and Replenishment (CPFR) in the Textile Supply Chain of Pakistan (Journal of Asian Development Studies, 2023)
The primary purpose of this paper is to find the effect of collaboration in the textile sector. The detailed study discusses the benefits of CPFR and defines the suitable structure of CPFR for Pakistan. The study comprises a review of different research articles for a clear understanding of collaboration and the impact of CPFR. The review suggests that CPFR provides the ultimate benefits to the supply chain of the textile sector when environmental uncertainties are present and also focuses on the textile cluster and its current supply chain practices. The review measures the critical variable of CPFR and its relationship with competitive performance. Also, it highlights the various issues in the demand collaboration process of the textile sector in Pakistan. The review provides a qualitative study of CPFR and a bird’s eye view of the scopes and benefits of CPFR for the textile sector.